Minimally Invasive Stabilization with or without Ablation for Metastatic Periacetabular Tumors. (7th July 2021) - English, D. Ian; Lea, William B.; King, David M.; Tutton, Sean M.; Neilson, John C.
Abstract : Background: Metastatic bone disease in the periacetabular region represents a potentially devastating problem for patients. Surgical treatment can offer pain relief and restore function. We describe a series of patients treated with minimally invasive osteoplasty and screw fixation with or without ablation. Methods: Thirty-eight patients with 16 different metastatic tumor subtypes were managed with osteoplasty and screw fixation with or without ablation at a single institution. A retrospective review was performed to determine functional outcomes with use of the 1993 Musculoskeletal Tumor Society (MSTS) score as well as changes in narcotic usage. Results: MSTS scores improved for all patients following surgery. Narcotic usage decreased in >80% of patients. Approximately half of the operations were outpatient procedures. Complications were minimal, there were no delays in chemotherapy or radiation due to surgical wound concerns, and there were no surgery-related deaths. The mean duration of follow-up was 9 months, with a 39% survival rate at the time of writing. Six of the 12 patients who survived for >1 year required additional procedures at a mean of 12 months (range, 4 to 23 months). Conclusions: Treatment of periacetabular metastatic disease with minimally invasive stabilization with or without ablation provides pain relief and functional improvement with lower complication rates than previously reported open reconstruction techniques. The minimally invasive approach allows for rapid initiation of chemotherapy and radiation. Patients with particularly aggressive cancers that are poorly responsive to systemic therapies and radiation may have progression of disease and may require additional procedures. Conversion to total hip arthroplasty was uncomplicated, and the cement and screw constructs were retained, providing a stable base for the arthroplasty reconstruction. Level of Evidence: Therapeutic Level IV . See Instructions for Authors for a complete description of levels of evidence.